Nimophulelani na umfazi: Ndiyindoda.: An investigation of the place of pastoral care in relation to both Jesus’ masculinity and amaXhosa masculinity. - Penxa-Matholeni, Nobuntu (Stellenbosch Theological Journal, 2021)
In 2019, the South African media put a spotlight on the brutal killings of women by men in the months of August and September. This femicide sparked conversations around masculinity which in turn spurred this article. Herein, I seek to investigate the space that will enable pastoral care to dialogue between Jesus' masculinity and the masculinity of umXhosa men. This will be done through a comparison of Jesus' words to the woman in Mark 14:6, which is included in the title of this paper, and the umXhosa word for masculinity, "ndiyindoda" (I am a man). The story of Jesus' healthy masculinity as God will be linked to amaXhosa masculinity. The aim of this article is to ascertain whether pastoral care can serve as a channel between these two masculinities. The relational indigenous methodology will be employed through narrative pastoral care. In that, narrative enables one to hear people's stories and link them to God's story.